The international politics of the Asia-Pacific - Yahuda, Michael (New York Routledge, 2011)
This fully revised third edition of Michael Yahuda's extremely successful textbook brings the region fully up-to-date, introducing students to the international politics of the Asia-Pacific region since 1945. As well as assessing the post-Cold War uncertainties that challenged the balance and power within the region, Yahuda also examines the first decade of the new millennium which includes no let up on the'war on terror', new political administrations in all the key player-states and increased cooperative security between some nations, polarized by volatile relationships between others. Analyzing politics in terms of global, regional and local trends, this new edition features: In-depth discussion of the Bush administration's legacy and where the Obama administration's vision takes their policy Analysis of post-Koizumi/post-Abe Japan Examination of the continued rise of China in terms of politics, security and economic dominance Ongoing debates concerning the'war on terror'and how this shifts, forms and reforms relationships Asia-Pacific security issues This new third edition will continue to be a core text for students of Asian politics, international relations and Cold War history.
Keywords: Asia sudoriental -- Política y gobierno -- 1945-; Asia oriental -- Política y gobierno; Asia oriental -- Relaciones exteriores; Asia sudoriental -- Relaciones exteriores; Libros electrónicos